Кон Јасна Котеска, Комунистичка интима: Për Јасна Котеска, Комунистичка интима - Angelovska, Despina; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2008)
Author(s): Despina Angelovska | Деспина Ангеловска Title (Macedonian): Кон Јасна Котеска, Комунистичка интима Title (Albanian): Për Јасна Котеска, Комунистичка интима Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 251-257 Page Count: 7 Citation (Macedonian): Деспина Ангеловска, „Кон Јасна Котеска, Комунистичка интима“, Идентитети: списание за политика, род и култура, т. 7, бр. 1-2 (лето 2008 - зима 2009): 251-257. Citation (Albanian): Despina Angelovska, „Për Јасна Котеска, Комунистичка интима“, përkthim nga Maqedonishtja Lindita Ahmeti, Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009): 251-257.